An Updated Model for Fast Total Solids Content Determination in Natural Rubber Latex Using Shortwave Near Infrared Spectroscopy - Sirisomboon, Panmanas (วารสารสมาคมวิศวกรรมเกษตรแห่งประเทศไทย, 2016)
<span style="line-height: 107%; font-family: 'Calibri',sans-serif; font-size: 14pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Cordia New'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: TH;">The analysis of total solids content (TSC) of Para rubber latex including field latex and concentrated latex, using near-infrared spectroscopy was carried out by a ultra violet/visible/near-infrared (UV/VIS/NIR) Spectrometer in transmittance mode over the wavelength range of 350–1100 nm. The original model provided the best accuracy of prediction was developed using the partial least square regression (PLSR) from the spectra which were pretreated by the smoothing and range normalization in the wavelength range of 700-950 nm. The slope, offset, correlation coefficient (r), standard error of prediction (SEP) and bias were 1.0084, -0.2332, 0.9940, 1.3611% and 0.1456%, respectively. The updated model was done by adding the 160 samples merged into the 280 original samples. The slope, offset, correlation coefficient (r), standard error of prediction (SEP) and bias were 0.9795, 0.7150, 0.9834, 1.6186% and -0.0802%, respectively. Therefore, the robust updated model by NIRS technique was more accurate and faster method for determining the TSC of Para rubber latex, for both field latex and concentrated latex.